The Significance of Introducing Permanent Assignments for Nursing Assistants at a Long-Term Care Setting on the Incidence Rate of Facility-Acquired Pressure Ulcers Among Elderly Patients - Mangaco-Borja, Erlynda (Elsevier, 2011)
Pressure ulcer prevalence remains a major health concern in long-term care facilities. The treatment of these pressure ulcers causes a financial drain on health care resources and adds potential costs for the family of the institutionalized elderly, according to the Agency for Healthcare Research and Quality. The prevention of pressure ulcer development continues to be an essential objective of caregivers for elderly people. This study demonstrated a correlation between the permanent assignment of nursing assistants and the prevention of pressure ulcers among the elderly in a nursing home.